2017
DOI: 10.1080/20009666.2017.1374111
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable vascular scaffold versus metallic stent in percutaneous coronary intervention: results of the AIDA trial

Abstract: Drug-eluting stents have significantly improved the long-term outcomes of percutaneous coronary intervention (PCI) by decreasing the excessive growth of neointima. However, conventional stents have some limitations. PCI with a bioresorbable vascular scaffold (BVS) has emerged as an alternative since the presence of the prosthesis in the coronary artery is transient. A US Food and Drug Administration advisory panel of experts recommended approval of BVS based on the analysis of its risks and rewards in July 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The clinical presentation is generally dependent on the degree of the shunt and the size of the fistula. Literature has shown potential complications, which include myocardial ischemia secondary to embolization or steal phenomenon and sudden cardiac death [6,7]. The closure of the fistula is recommended when it is symptomatic, while the treatment in asymptomatic patients remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical presentation is generally dependent on the degree of the shunt and the size of the fistula. Literature has shown potential complications, which include myocardial ischemia secondary to embolization or steal phenomenon and sudden cardiac death [6,7]. The closure of the fistula is recommended when it is symptomatic, while the treatment in asymptomatic patients remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The closure of the fistula is recommended when it is symptomatic, while the treatment in asymptomatic patients remains controversial. Large coronary fistulas should be closed by transcatheter or surgical treatment, regardless of symptoms, while small to moderate size fistulas should be treated only if they cause symptoms [6][7][8][9]. Treatment for clinically significant CAF have focused on surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…These are composed of a temporary scaffold designed to provide a platform for drug elution but then degrade over time with no material left behind. Studies have shown that these scaffolds fully resorb after 3 years, leaving the vessel in its native state [ 33 ]. However, the enthusiasm for these new stents has been tempered by concerns over increase in stent thrombosis, leading to limitations in use in Europe and the United States [ 34 ].…”
Section: Percutaneous Coronary Interventionsmentioning
confidence: 99%
“…ICD placement is the only proven mortality benefit treatment for ARVC [11,23,24,27,29,5254]. ICD placement can also be used for primary or secondary prevention [23,24,54].…”
Section: Icd Placementmentioning
confidence: 99%